PCaLiStDB: a lifestyle database for precision prevention of prostate cancer. (16th January 2020) - Chen, Yalan; Liu, Xingyun; Yu, Yijun; Yu, Chunjiang; Yang, Lan; Lin, Yuxin; Xi, Ting; Ye, Ziyun; Feng, Zhe; Shen, Bairong
Abstract: The interaction between genes, lifestyles and environmental factors makes the genesis and progress of prostate cancer (PCa) very heterogeneous. Positive lifestyle is important to the prevention and controlling of PCa. To investigate the relationship between PCa and lifestyle at systems level, we established a PCa related lifestyle database (PCaLiStDB) and collected the PCa-related lifestyles including foods, nutrients, life habits and social and environmental factors as well as associated genes and physiological and biochemical indexes together with the disease phenotypes and drugs. Data format standardization was implemented for the future Lifestyle-Wide Association Studies of PCa (PCa_LWAS). Currently, 2290 single-factor lifestyles and 856 joint effects of two or more lifestyles were collected. Among these, 394 are protective factors, 556 are risk factors, 45 are no-influencing factors, 52 are factors with contradictory views and 1977 factors are lacking effective literatures support. PCaLiStDB is expected to facilitate the prevention and control of PCa, as well as the promotion of mechanistic study of lifestyles on PCa. Database URL: http://www.sysbio.org.cn/pcalistdb/